Genetic variability, heritability, and diversity analysis in short day tropical onion (Allium cepa) - DANGI, RAVINDRA; KUMAR, AMRENDER; KHAR, ANIL (The Indian Journal of Agricultural Sciences, 2018)
The main aim of the present investigation was to assess the degree of variability, heritability and genetic advance in onion (Allium cepa L.) using 13 quantitative and four biochemical traits. PCV was higher than GCV for all the traits but the difference was less in plant height, pyruvic acid, leaf length, number of leaves, pseudostem length, pseudostem width, leaf width and total phenols indicating higher contribution of genotypic effect towards phenotypic expression. Highest heritability was observed for plant height, number of leaves, leaf length, leaf width, pseudostemlength, pseudostem diameter, total phenols and pyruvic acid. High heritability along with high genetic advance as percent of mean was recorded in number of leaves, leaf length, leaf width, pseudostem length, pseudostem diameter, total phenols and pyruvic acid indicating the presence of additive gene action for the expression of these traits. Based on Euclidean distance and Ward’s minimum variance, all accessions were clustered into four groups. Cluster I comprised of accessions with highest yield, yield related traits and high pungency. Cluster II was the largest cluster and composed of accessions having highest TSS and dry matter content. Cluster III was the smallest cluster comprising ofaccessions having highest polar diameter and total phenols. Cluster IV comprised of accessions having low yielding potential. Five principal components (PC1 to PC5), having latent roots greater than one, accounted for 78.5% total variation. Cluster analysis and Principal component analysis (PCA) were in agreement for assigning genotypes into four clusters. In the first principal component, plant height, leaf length and pseudostem diameter were the most contributing traits, whereas dry matter, total soluble solids (TSS) and pyruvic acid were the principal traits of the second principal component. Based on squared cosine value (Cos2) for variables, average bulb weight, gross yield and marketable yield in positive direction and plant height, leaf length and pseudostem width in negative direction, were the major contributing traits. Squared cosine value (Cos2) for individual factor determined that Superex and Black Gold were the most prominent genotypes contributing towards PCA. This study would provide a better opportunity to select potential genotypes for yield related traits and help breeders in precise selection of promising diverse parents for purposeful heterosis breeding.